IMPLEMENTASI PENGANGGARAN BERBASIS KINERJA: (STUDI PADA SATUAN KERJA PUSAT SURVEI GEOLOGI) - SUPRAYOGI, SUPRAYOGI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
This research discuss the Application and Implementation of Performance Based Budgeting at Center for Geological Survey. Material study in this case consists of budgetary process including planning, implementation, and evaluation of performance measurement and reporting. This case of study illustrates the obstacles encountered in the process of budgeting, implementation and evaluation. With a qualitative research, the data obtained with the natural setting. Data was collected by questionnaire, observation, interviews and documentation. The collected data was analyzed by the triangulation method using descriptive paradigm. Theoretical approachment used to describe an intense understanding of the budgeting process in the Center for Geological Survey. The result of this study indicate that in general the ideal performance-based budgeting has not been reached, the employees and leaders do not understand the meaning of Performance-Based Budgeting. There are some error in the process of budgeting, including planning, implementation, and evaluation of performance measurement and reporting. Lack of rewards and punishment system, an Internal Control and work ethic causes of the problem aboved.